Application Of Gandasil D Fertilizer on The Freshness of Chrysanthemum Flowers In Hydrogel Media - Fatimatuz Zuhro; Sarwo Danuji (PROGRAM STUDI PENDIDIKAN BIOLOGI, 2021)
Chrysanthemum sp. is one of the popular types of cut flowers and is in great demand by consumers because of its attractive shape, color, and varying sizes. This study aims to determine the effect of Gandasil D and its application method in maintaining the freshness of chrysanthemum flowers in hydrogel media. This study used a completely randomized design consisting of 2 treatment factors, namely the concentration treatment of Gandasil D (0%, 0.5%, and 1%) and the application of Gandasil D (soaking, spraying, and a combination of both). Parameters observed, among others; leaf wilting rate, flower freshness duration, leaf freshness duration, and flower wilting rate. The results of this study showed that the concentration of Gandasil D treatment had no significant effect on the freshness of chrysanthemum flowers, except for the length of leaf freshness parameter which showed that the concentration of Gandasil D 1% produced the longest leaf freshness among other treatments. The Gandasil D application method has a significant effect on the freshness of chrysanthemums. The single treatment of immersion or spraying resulted has a longer average flower freshness than the combination treatment, although the average value between soaking and spraying was not significant. The combination of concentration treatment and application method of Gandasil D had no significant effect on the freshness of chrysanthemums, except for the length of flower freshness parameter.